Exploration of Migrants‟ Social Life : A Case Study on Bangladeshi Temporary Contract Worker‟s in Malaysia - Md. Sayed, Uddin; Adam Andani, Mohammed (Macrothink Institute, 2020)
Migrant workers are a different community as they have leave their origin country and entered to a new nation where the social life they had to dealt with differently. Because social life is very important as an individual has hold an ideology, special socio-cultural background and religious affiliation. It is, thus, an important phenomena to assess the perception of migrants about social life, the nature of their involvement in the social setting, the meaning they attach to it and their priorities and preferences in interacting with others. The study is based on the face-to-face interview of 100 Bangladeshis migrant workers who were selected according to two stage sampling procedure. On one stage, an area where Bangladeshi workers reside was selected through random sampling procedure. On the second stage, 100 respondents were selected from the area according to purposive and snowball sampling procedures. The study suggested that adequate measures should be taken to provide pre-departure training on job and Host County‟s culture to the expected migrant workers.